STUDY ON THE EFFECT OF NANOPARTICLES ON THE RESISTIVITY OF POROUS MEDIUM CONTAINING TWO-PHASE FLUID - MOHAMAD NOOR, MOHD ZULKIFLI (2021)
Nanoparticles have grown in importance over the last decade with significant consumer and industrial applications. The adverse influence of oil on nanoparticles stability is a stumbling block to their use in oil recovery. The zeta potential was used as a screening part for nanoparticles as a contrast agent in this study. The injection of nanoparticles in nanofluid will differentiate the low contrast zones. The nanoparticles were first screened based on their philicities, shapes, and size. The philicities of the nanoparticles were determined using a two-phase layer static test procedure. The zeta potential was then determined using Anton Paar SurPASS electrokinetic analyzer. The sand pack displacement unit was used to determine nanoparticle injection and the benchtop permeability system unit was used to establish a baseline value.